Evaluasi Penggunaan QRIS pada m-Banking Bank Syariah: Pendekatan Technology Acceptance Model - Waluyo (Mutanaqishah: Journal of Islamic Banking, 2022)
This study aims to evaluate transactions using QRIS in mobile banking of Islamic banks. The approach is carried out with the Theory of Acceptance Model (TAM) which integrates usefulness, ease of use and trust in the decision to use QRIS. The respondents who were successfully collected were 140, with technical random sampling in the community in Surakarta. The data analysis technique uses multiple regression analysis with smartPLS. The results show that all variables affect the decision to use QRIS in islamic bank banking cars. Although the results show an influence, there are findings that there is a need for massive socialization of both merchants and users so that the cashless movement can run optimally. In addition, it is necessary to equalize the internet so that the QRIS feature can be felt throughout the region.